A fluorescent reporter system for anaerobic thermophiles - Hocq, Rémi; Bottone, Sara; Gautier, Arnaud; Pflügl, Stefan (Frontiers in Bioengineering and Biotechnology, 2023)
Owing to their inherent capacity to make invisible biological processes visible and quantifiable, fluorescent reporter systems have numerous applications in biotechnology. For classical fluorescent protein systems (i.e., GFP and derivatives), chromophore maturation is O2-dependent, restricting their applications to aerobic organisms. In this work, we pioneered the use of the oxygen-independent system FAST (Fluorescence Activating and absorption Shifting tag) in the thermophilic anaerobe Thermoanaerobacter kivui. We developed a modular cloning system that was used to easily clone a library of FAST expression cassettes in an E. coli – Thermoanaerobacter shuttle plasmid. FAST-mediated fluorescence was then assessed in vivo in T. kivui, and we observed bright green and red fluorescence for cells grown at 55 °C. Next, we took advantage of this functional reporter system to characterize a set of homologous and heterologous promoters by quantifying gene expression, expanding the T. kivui genetic toolbox. Low fluorescence at 66 °C (Topt for T. kivui) was subsequently investigated at the single-cell level using flow cytometry and attributed to plasmid instability at higher temperatures. Adaptive laboratory evolution circumvented this issue and drastically enhanced fluorescence at 66 °C. Whole plasmid sequencing revealed the evolved strain carried functional plasmids truncated at the Gram-positive origin of replication, that could however not be linked to the increased fluorescence displayed by the evolved strain. Collectively, our work demonstrates the applicability of the FAST fluorescent reporter systems to T. kivui, paving the way for further applications in thermophilic anaerobes.